2010
DOI: 10.1002/jsfa.3953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dehulling on the apparent metabolisable energy and ileal amino acid digestibility of grain legumes for broilers

Abstract: Dehulling of grain legumes is nutritionally beneficial in view of the improved amino acid concentrations and metabolisable energy values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
3
26
2
Order By: Relevance
“…32 The notable protein content of MD lupin seeds has nutritional significance, since moderate intake of these grains will greatly increase the total dietary protein intake. Hence, its utilisation as an alternative protein source in poultry formulation will reduce over-dependence on conventional plant protein such as soybean meal.…”
Section: Resultsmentioning
confidence: 99%
“…32 The notable protein content of MD lupin seeds has nutritional significance, since moderate intake of these grains will greatly increase the total dietary protein intake. Hence, its utilisation as an alternative protein source in poultry formulation will reduce over-dependence on conventional plant protein such as soybean meal.…”
Section: Resultsmentioning
confidence: 99%
“…Lupin kernels were evaluated in the latter study, whereas seeds with hulls were used in this study and the dilution effect of hulls may explain, at least partly, the observed discrepancy. The proportion of hulls in the lupin seeds can be as high as 0.32, and Nalle et al (2010b) reported that dehulling of Australian sweet lupin seeds resulted in marked reductions in NSP contents and improved AME values.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that, when diets are balanced in terms of metabolisable energy and digestible amino acids, white lupins can be included at a level of 200 g/kg in broiler starter diets, with no detrimental effect on performance. Further studies are warranted to investigate the possibility of higher levels of inclusion of white lupins in broiler diets through the removal of hulls (Nalle et al, 2010b) and/or the use of NSP-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Lupin by-products are generated during feed production for pigs and poultry, as de-hulling lupin seeds is important for these species in terms of increasing their nutritive value (Mieczkowska et al, 2005;Písaříková and Zralý, 2009;Nalle et al, 2010). Volek et al (2013) showed that white lupin hulls seem to be suitable for use in rabbit diets.…”
Section: Introductionmentioning
confidence: 99%